2021
DOI: 10.1111/bph.15455
|View full text |Cite
|
Sign up to set email alerts
|

The role of cGMP signalling in auditory processing in health and disease

Abstract: cGMP is generated by the cGMP-forming guanylyl cyclases (GCs), the intracellular nitric oxide (NO)-sensitive (soluble) guanylyl cyclase (sGC) and transmembrane GC (e.g. GC-A and GC-B). In summarizing the particular role of cGMP signalling for hearing, we show that GC generally do not interfere significantly with basic hearing function but rather sustain a healthy state for proper temporal coding, fast discrimination and adjustments during injury. sGC is critical for the integrity of the first synapse in the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 155 publications
(314 reference statements)
0
3
0
Order By: Relevance
“…Vasopressin and oxytocin are expressed not only in the limbic forebrain (Cilz et al, 2019) but also in the cochlea (Reuss et al, 2009). Oxytocin also stimulates soluble guanylate cyclase and increases intracellular cGMP (Porzionato et al, 2010;Conrad et al, 1993), the signaling cascade that was shown to act on auditory nerve processing (Chumak et al, 2016;Marchetta et al, 2020Marchetta et al, , 2021.…”
Section: Relation Of the Finding To Corticosterone Blood Level Changesmentioning
confidence: 99%
“…Vasopressin and oxytocin are expressed not only in the limbic forebrain (Cilz et al, 2019) but also in the cochlea (Reuss et al, 2009). Oxytocin also stimulates soluble guanylate cyclase and increases intracellular cGMP (Porzionato et al, 2010;Conrad et al, 1993), the signaling cascade that was shown to act on auditory nerve processing (Chumak et al, 2016;Marchetta et al, 2020Marchetta et al, , 2021.…”
Section: Relation Of the Finding To Corticosterone Blood Level Changesmentioning
confidence: 99%
“…A central role for CNP has been established in relation to its NPR-B/cGMP-mediated promotion of axonal bifurcation in somatosensory neurons and auditory function ( Dumoulin et al, 2021 ; Marchetta et al, 2022 ). However, a wider contribution of the peptide to the physiological regulation of cognition, motor function and BBB integrity has not been fully elucidated, despite previous work hinting at a role for CNP in these settings ( Vigne and Frelin, 1992 ; Pedram et al, 2002 ; Barmashenko et al, 2014 ; Rapley et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the eye, the activation of GPCRs via the PLC/IP3 pathway occurs by means of the cells containing melanopsin, such as the ganglion cells of the iris, whilst the cells of the retina containing rhodopsin and the cells of the auricular cochlea follow a different pathway, via PDE/cGMP [112,113]. In this case, the protons are generated by the hydrolysis of cGMP and the dissociation of acid glutamate, as described below in paragraph 2.…”
Section: Pre-synaptic Transmission Of the Impulse In Sensory Neuronsmentioning
confidence: 99%